(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2015)
India is emergingas a prime destination for health and contributing a lot towards the social-economicdevelopment of the society by enhancing employment opportunities and anincrease in foreign exchange earnings and helping in uplifting the livingstandards of the host community by developing infrastructure and high qualityeducation system. Today Indian hospitals are well equipped with the latesttechnology and houses highly qualified and experienced staff who can providetimely and quality medical treatment to patients.